Students as co-producers of education : cases from student participation in the educational programs of a Swedish university - Halvarsson, Ylva; Lohela, Miia-Ilona (2009)
The market for all types of services has grown rapidly and its dominance can be noted in economies worldwide. Services as a dominant force have also drawn attention to the problems and issues involved. People and processes are two factors that play important roles in the service context. Interaction between organizations, its employees and customers leads to the service outcome. In some services, customers are required to participate actively to enable service production. In other words, the customer becomes a co-producer of the service delivery. Services can be categorized into various levels depending on the degree of customer participation. In this study, university education, the type of service which demands high level customer/student participation was chosen as the service to be investigated primarily due to insufficient existing research. The purpose is thus to investigate Swedish universities’ involvement of students as co-producers in the educational programs. A qualitative multiple case research approach is used, and the cases consist of five educational programs at Luleå University of Technology. Findings indicate that students can be seen as having two specific responsibilities within an educational program: the students must participate in their education in order to improve their own learning as well as contribute to improve the design of the program. Moreover, university education cannot be created without the students’ active participation. The study also found that there exists several different ways to motivate the students to participate and socially engage in the educational programs. Furthermore, attracting and retaining the right types of students is of importance for the university programs. Several types of methods are applied in order to reward students for their participation. Finally, university programs gain student feedback of their services continuously and to this end strive for more applicants to their programs. Validerat; 20101217 (root)